Role of narrow band imaging in the detection of mucosal lesions of head and neck - Bhandari, Pranay; Sachdeva, Kavita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Head and neck mucosal lesions are difficult to diagnose at early stage; therefore, they usually present at an advance phase. Narrow Band imaging (NBI) first came to use around 2005 and became one of the most used technologies for image enhanced endoscopy. Material and method: In order to identify best method for early detection of mucosal lesion of head and neck, we examined patients with suspected lesions first under white light endoscopy then under NBI endoscopy. Patients under-went biopsy thereafter, and results were compared. Our aim was to evaluate the role of NBI as a screening tool in the early detection of mucosal lesions of head and neck. Result: It was observed that NBI is useful tool in identifying mucosal lesions of head and neck early. 71 patients were included in our study and it was observed that NBI endoscopy shows 100% sensitivity, 96.36% specificity and 97.18% accuracy in identifying benign lesions. It shows 100% sensitivity, 94.74% specificity and 98.59% accuracy in identifying malignant lesions. Conclusion: In our study we came to conclusion that NBI is very promising tool for early screening purposes of mucosal lesions of head and neck which were missed in routine examination.